30. COMT Val158Met and MTHFR C677T Moderate Risk of Schizophrenia in Response to Childhood Trauma - Debost, Jean-Christophe (Schizophr Bull, 2017)
Background: Childhood trauma is a risk factor in the etiology of schizophrenia. Mesolimbic dopamine sensitization has been hypothesized to be a mediating factor of childhood trauma on the risk of schizophrenia. Activity of catechol-O-methyltransferase (COMT) Val158Met increases mesolimbic dopamine signaling, and COMT activity may be further regulated by methylenetetrahydrofolate reductase (MTHFR) C677T. The objective of the present study was to investigate the hypothesized three-way interaction between childhood trauma, COMT and MTHFR. Methods: We conducted a nested case–control study on individuals born after 1981, linking Danish nationwide population-based registers to obtain information on genetics and exposure to childhood trauma. The study included 1699 schizophrenia cases and 1681 controls. We used an additive genetic model and conditional logistic regression to estimate interactions between allele count and exposure status. Incidence rate ratios (IRRs) were estimated with corresponding 95% confidence intervals (95% CI). Results: Childhood trauma was robustly associated with schizophrenia. No main genetic effects were observed. MTHFR C677T increased schizophrenia risk in a dose-dependent manner per MTHFR T-allele (P = .005) consequent upon trauma exposure. In the 3-way interaction model, the risk was further increased in a dose-dependent manner per high-activity COMT Val-allele. Hence, exposed COMT Val/Met and MTHFR T/T carriers had an IRR of 2.34 (1.51–3.61). Additional adjustments for polygenic risk score, ancestry and parental history of mental illness, attenuated the results with the interaction being only marginally significant. Conclusion: MTHFR C677T and COMT Val158Met interact with childhood trauma to increase risk of schizophrenia.